Targeting Cyclin-Dependent Kinases for Treatment of Gynecologic Cancers - Lin, Z. Ping; Zhu, Yong-Lian; Ratner, Elena S. (Frontiers in Oncology, 2018)
Ovarian, uterine/endometrial, and cervical cancers are major gynecologic malignancies estimated to cause nearly 30,000 deaths in 2018 in US. Defective cell cycle regulation is the hallmark of cancers underpinning the development and progression of the disease. Normal cell cycle is driven by the coordinated and sequential rise and fall of cyclin-dependent kinases (CDK) activity. The transition of cell cycle phases is governed by the respective checkpoints that prevent the entry into the next phase until cellular or genetic defects are repaired. Checkpoint activation is achieved by p53- and ATM/ATR-mediated inactivation of CDKs in response to DNA damage. Therefore, an aberrant increase in CDK activity and/or defects in checkpoint activation lead to unrestricted cell cycle phase transition and uncontrolled proliferation that give rise to cancers and perpetuate malignant progression. Given that CDK activity is also required for homologous recombination (HR) repair, pharmacological inhibition of CDKs can be exploited as a synthetic lethal approach to augment the therapeutic efficacy of PARP inhibitors and other DNA damaging modalities for the treatment of gynecologic cancers. Here, we overview the basic of cell cycle and discuss the mechanistic studies that establish the intimate link between CDKs and HR repair. In addition, we present the perspective of preclinical and clinical development in small molecule inhibitors of CDKs and CDK-associated protein targets, as well as their potential use in combination with hormonal therapy, PARP inhibitors, chemotherapy, and radiation to improve treatment outcomes.